Perspectives and Insights on Training Veterinary Medicine and Animal Science of Students Enrolled in an Animal Nutrition Course in Colombia - Roa Vega , María Ligia (2026)
The Veterinary Medicine and Animal Science (MVZ) program at UNILLANOS has encountered difficulties in integrating fundamental Natural Sciences with practical sciences in areas such as animal health, animal production, and rural extension. The MVZ curriculum encompasses an Animal Nutrition course vital for animal production and prospective career endeavors. This project aimed to develop pedagogical methodologies for MVZ academic training, based on the knowledge acquired by students in the Animal Nutrition course and its practical implementation in the livestock industry. Research is based on an interpretive framework, employing a descriptive qualitative methodology and utilizing the phenomenological approach. Consequently, the results of this study may enhance understanding of this phenomenon. Data collection involved a semi-structured interview conducted among 60 students over the years 2023 and 2024. The data collected via the instrument was categorized into the following segments: prior knowledge, study of Animal Nutrition, socio-productive context: application of knowledge, cognitive, technical, and social domains, and relevance to livestock activities in their professional practice. The findings of this study indicate that students recognized biology, chemistry, biochemistry, physiology, and mathematics as essential disciplines for engaging with the Animal Nutrition course. Furthermore, they indicated that the instruction of this course requires an integration of theory and practice, promoting student autonomy through guides, seminars, and projects, while fostering logical reasoning to strengthen active learning within an effective framework. Students identified innovative methodologies including precision nutrition, gastrointestinal microbiology, circular bioeconomy, genomics, and low-emission nutrition, all of which contribute to the advancement of sustainability and animal welfare. Therefore, it is imperative for educators to remain updated regarding the use of ICTs in planning nutritional programs tailored to specific production systems, thereby fostering contextualized and effective teaching methodologies. It was concluded that these innovative techniques can be included into multidisciplinary projects, enabling students to use their knowledge in real contexts within cattle production.